UNMET NEEDS OF LESBIAN WOMEN IN BREAST CANCER TREATMENT - Carolina de Souza; Manoel Antônio dos Santos (Psicologia & Sociedade)
Abstract Women whose sexuality deviate from the heteronormative standard, such as lesbians and bisexuals, go unnoticed by health services. This study aims to describe the experiences of discrimination suffered by a lesbian woman with breast cancer and her partner during their oncological treatment journey. A qualitative case study based on in-depth interviews was conducted with two lesbian spouses. Thematic analysis allowed the construction of thematic axes. The results showed that the vulnerability process of the spouses was amplified by the need to defend themselves against constant attacks on their identities. The invisibility and discrimination of lesbian women in the oncology care network has contributed to multiplying the unmet health needs, worsening the already tenuous link with health professionals. Addressing the disparities experienced by lesbian women in health services is a challenge for the effective implementation of the human rights agenda.